What Can Affect Employee Perfomance? An Empirical Study Retail Jewellery Company In North Jakarta, Indonesia - Chintya Fransisca; Danial Thaib (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
This study aims to analyze the effect of work motivation and work environment on employee performance with job satisfaction as a mediating variable among Adelle Jewellery employees in North Jakarta. This research employs a quantitative approach using a survey method, involving 100 employees as the sample. Data collection was conducted through questionnaires measured using a Likert scale. The collected data was then analyzed using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method. The results show that work motivation and work environment have a significant impact on employee performance. Additionally, job satisfaction was found to partially mediate the effect of work motivation and work environment on employee performance. This means that enhancing work motivation and creating a conducive work environment can increase job satisfaction, which in turn, improves employee performance. This research provides important insights for Adelle Jewellery's management in understanding the factors that influence employee performance. The practical implications of these findings highlight the importance of management focusing on improving work motivation and creating a supportive work environment to enhance employee satisfaction and performance. The study also suggests the need for further research to explore other factors that may influence employee performance and to test similar models in different industries and contexts.